(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
Teacher identity has received recent attention, yet instruments assessing it lack in agreed constructs and repeated reliabilities. The present study thus accommodated the need for a comprehensive and replicable measure of teacher identity. A teacher identity inventory (TII) was constructed entailing three core components (teacher self-efficacy, organizational commitment, and job satisfaction). To validate it, three independent samples partook in three waves of study. Study 1 ( N=236 year-3 prospective teachers) generated a three-factor structure entailing seven scales through an exploratory analysis. Study 2 (N=1,102 year-4 prospective teachers) cross-validated the factor structure between a calibration sample (N=539) and a validation sample (N=563). A 34-item factor structure was finalized. Study 3 ( N=232 beginning teachers) tested and verified the utility of the TII by examining how it was correlated with and regressed on the Job Demands-Resources Inventory (JD-RI). Limitations and implications for future research are discussed.